2022
DOI: 10.1111/jam.15479
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an alcohol-based surface disinfectant formulation against human norovirus

Abstract: Aim To evaluate the anti‐noroviral efficacy of PURELL® surface sanitizer and disinfectant spray (PSS, an alcohol‐based formulation) using human norovirus GII.4 Sydney [hNoV, by RT‐qPCR and human intestinal enteroid (HIE) infectivity assay] and its cultivable surrogate, Tulane virus (TuV, infectivity assay), compared to sodium hypochlorite (NaOCl) solutions. Methods and Results PSS efficacy was evaluated in suspension and on surfaces [stainless steel (SS)] using ASTM methods. Results were expressed as log10 red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…1 to 3 ). While this is only the second set of findings for this particular product ( 14 ), the results for the other chemistries are consistent with previous reports ( 11 , 12 , 14 ). For example, NaOCl solutions containing 200 ppm free chlorine have previously been shown to be minimally effective against hNoVs after even a 5-min contact time ( 12 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1 to 3 ). While this is only the second set of findings for this particular product ( 14 ), the results for the other chemistries are consistent with previous reports ( 11 , 12 , 14 ). For example, NaOCl solutions containing 200 ppm free chlorine have previously been shown to be minimally effective against hNoVs after even a 5-min contact time ( 12 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is supported by previous research in which deformation of hNoV-like particles occurred when exposed to alkaline conditions ( 32 , 33 ). Given previously observed synergistic antiviral effects of ethanol and high pH for hNoVs ( 14 , 34 ), the combination of ethanol and high pH is likely the primary driver of this product’s efficacy, resulting in further disruptions to hydrogen bonding in addition to stabilizing hydrophobic residues exposed during protein denaturation. ( 35 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 54 An in vitro experimental model by Costantini et al 56 using HIE showed complete suppression of norovirus GII strains in fecal specimens with as low as 50 parts per million (ppm) of chlorine solution. 56 Comparison of a commercial-grade alcohol-based surface disinfectant (‘PSS’) containing 29.4% ethanol (pH 12.6–12.9) with sodium hypochlorite solutions of various concentrations (1000–5000 ppm) was performed by Escudero-Abarca et al 57 In vitro assays (suspension and soil on stainless steel surface) consistently showed higher genome-equivalent copy number reduction for sodium hypochlorite as opposed to PSS, although PSS showed similar efficacy comparable to 1000–5000 ppm chlorine, when 60-s contact time was applied with high soil load. The authors suggested loss of attachment efficiency by viral particles and capsid disintegration due to the alkaline nature of the PSS as the mechanism of antiviral property.…”
Section: Infection Prevention and Controlmentioning
confidence: 99%
“…The authors suggested loss of attachment efficiency by viral particles and capsid disintegration due to the alkaline nature of the PSS as the mechanism of antiviral property. 57 Sato et al 58 argued that the virucidal process involves protein denaturation rather than de-lipidation. Incubation of norovirus in alkaline solution-only, acidic solution-only, or alcohol-only did not demonstrate significant virucidal activity compared to control.…”
Section: Infection Prevention and Controlmentioning
confidence: 99%